2017
DOI: 10.2174/1871524916666160823121854
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer, Antioxidant and Cytotoxic Potential of Thymol in vitro Brain Tumor Cell Model

Abstract: In a conclusion, these results confirm that THY may have antiproliferative potential against brain tumor cells involving oxidative alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…This report clearly revealed that thymol is a potent anticancer and antiproliferative agent (Aydin et al, 2016). …”
Section: Thymol In Cancer Cellsmentioning
confidence: 79%
See 2 more Smart Citations
“…This report clearly revealed that thymol is a potent anticancer and antiproliferative agent (Aydin et al, 2016). …”
Section: Thymol In Cancer Cellsmentioning
confidence: 79%
“…Thymol (400 mg/L) decreased cell proliferation in cultured neuroblastoma cells (N2a cells) whereas thymol (19, 25, and 50 mg/L) increased the total antioxidant capacity in rat neurons but not in N2a cells. This report clearly revealed that thymol is a potent anticancer and antiproliferative agent ( Aydin et al, 2016 ).…”
Section: Thymol In Cancer Cellsmentioning
confidence: 79%
See 1 more Smart Citation
“…From nine plant species only C. armena and T. transcaucasicus showed comparatively strong antioxidant, as well as high‐to‐moderate cytotoxic activities. Some of identified main terpenes and polyphenols, such as β‐caryophyllene, kaempferol, quercitrin, apigenin, hyperoside and ursolic acid in C. armena and borneol, carvacrol, thymol, linalool, geraniol, 1,8‐cineole, rosmarinic acid, quercetin and caffeic acid in T. transcaucasicus were found to have antioxidant and cytotoxic activities. It should also be mentioned that borneol, linalool and rosmarinic acid, like plant extracts of C. armena and T. transcaucasicus in this study, showed similar cytotoxic activity against HepG2 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Thymol has demonstrated antioxidant effects in mouse neuron cultures (10, 25, and 50 mg/L) [266], and presents excellent hydroxyl radical elimination capacity [267]. Thymol increases antioxidant enzyme levels, for example SOD, GPx, CAT, and GST, and non-enzymatic antioxidants such as vitamins C and E [268].…”
Section: Thymolmentioning
confidence: 99%